2017
DOI: 10.1175/jtech-d-16-0141.1
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Calculations at C-Band for Asymmetric Raindrops Reconstructed from 2D Video Disdrometer Measurements

Abstract: The distribution of raindrop shapes is well known to be important in deriving retrieval algorithms for drop size distribution parameters (such as the mass-weighted mean diameter) and rain rate, as well as for attenuation correction using the differential propagation phase constraint. While past work has shown that in the vast majority of rain events the most “probable” shapes conform to those arising primarily from the axisymmetric (2,0) oscillation mode, a more recent event analysis has shown that drop collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Regarding (i), even though it is assumed (e.g., [24]) that horizontal velocities of precipitation particles do not differ from prevalent wind velocities (e.g., [24,32]) during steady conditions, it is only the 2DVD instrument which is capable of providing direct observational evidence of this in natural rain. It is consistent with previous studies [11,33] from a line convection event and a hurricane event which showed excellent agreement of the 2DVD-based drop horizontal velocities at near-ground level with the wind measurements at 10 m height. Currently, a 3D sonic anemometer has been installed at the UAH site to measure the ambient winds and turbulent intensity…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding (i), even though it is assumed (e.g., [24]) that horizontal velocities of precipitation particles do not differ from prevalent wind velocities (e.g., [24,32]) during steady conditions, it is only the 2DVD instrument which is capable of providing direct observational evidence of this in natural rain. It is consistent with previous studies [11,33] from a line convection event and a hurricane event which showed excellent agreement of the 2DVD-based drop horizontal velocities at near-ground level with the wind measurements at 10 m height. Currently, a 3D sonic anemometer has been installed at the UAH site to measure the ambient winds and turbulent intensity…”
Section: Discussionsupporting
confidence: 92%
“…Because both the H and V radar cross sections for any given drop will vary with the look angle, its differential reflectivity will also have a φ variation. This has been illustrated in [11] in terms of the complex scattering amplitudes for both polarizations (see their Figure 7 where φ was varied from 0 to 360° in the horizontal plane).…”
Section: Results For Individual Particlesmentioning
confidence: 95%
See 2 more Smart Citations
“…A relatively recent advance has been the use of 2DVD in reconstructing the 3D shapes of natural rain drops even if they are asymmetric [6], [7], and further to calculate the scattering matrices of such asymmetric (and the detected symmetric shape) drops using advanced electromagnetic scattering codes [8], [9]. This enables simulation of what is termed 'drop-by-drop' integration to arrive at the radar reflectivity, the differential reflectivity and the copolar correlation coefficient [10].…”
Section: Introductionmentioning
confidence: 99%